A Terracotta Treasure at Assos - Tuna Şare Ağtürk; Nurettin Arslan (Les Carnets de l’ACoSt)
During the summer of 1995, Turkish archaeologists discovered a unique Late Classical tomb in the Western Necropolis of Assos. A modestly designed cist grave, Tomb 4 surprised excavators with the richest cache of grave goods ever found at the ancient city. The 62 well-preserved artifacts, which date from the 4th century BCE, when Aristotle's school of philosophy was active at Assos, consist of terracotta figurines, gold and bronze jewelry, and vases.